Secant Condition Free of a Spectral Hestenses-Stiefel (SHS) Conjugate Gradient Method and its Sufficient Descent Properties - Abbas Yakubu, Usman; Mamat, Mustafa; Afendee Mohamed, Mohamad; Liza Ghazali, Puspa; Rivaie, Mohd (International Journal of Engineering and Technology, 2026)
The conjugate gradient method have been used widely to solve unconstrained minimization problems as a result of less storage locations and less computational expensive in dealing with the large-scale problems. In this work, we suggested a spectral HS conjugate gradient method without employing the secant condition and use some unconstrained problems with many variables to prove its sufficient descent as well as global convergence, the results is certified by apply exact line search procedure.